IOT based water level and quality monitoring system in overhead tanks - K. Raghava Rao, Dr; Srinija, Sanagala; Hima Bindu, Kukkala; Satish Kumar, D (International Journal of Engineering and Technology, 2018)
Water is most profitable and valuable source since it is the fundamental need of all the individuals. Now a day we are facing many issues regarding water wastage and quality monitoring in tanks. This paper proposes a proficient method to water level and quality observing in the overhead tanks to lessen the present water wastage and give better water quality. The venture is about overhead tank checking framework that is we screen the level of water in the overhead tank and furthermore we decide nature of water. Firstly, we have the issue of filling the tanks which are situated far, and for this we have executed a little hypothesis that we put level sensors in the tank, that level sensors detect the water level in the tank and sends us message about water level in the tank. Also, the second preferred standpoint is that really, we utilize different quality parameter sensors like pH and turbidity sensors to screen the water quality in the tank. In light of level of water, we can choose how much measure of water is required for specific area and give adequate measure of water as opposed to squandering water. The Raspberry Pi B+ is utilized as core controller. The composed framework applies to an IOT module for getting to sensor information from center controller to cloud. The sensor information can be seen on cloud. At last information will be assembled and through Wi-Fi information can be seen on versatile device through android app. Based on data in the app workers will be sent to clean the tank This proposed framework is a minimal effort, wireless, multi-sensor arrange for exact water monitoring in tanks.Â Â